Reorientasi Strategi Pembangunan Ekonomi yang Berorientasi pada Rakyat - Hamid, Edy Suandi (Unisia, 2016)
The discourse on people' economy in crisis and in the strong wave of reform movement is undoubtedly relevant. This is because of impact of the crisis on the people economy which is extremely huge. This article describes what so called the "people economy" and how the system vis a vis the market system of economy. Further, this article also discusses how the economic gap happens in Indonesia and recommends a system which is feasible to cope with it.